A STUDY ON THE LITERACY-RICH CLASSROOM ENVIRONMENT AT BILINGUAL KINDERGARTEN SINGARAJA BALI - N.M.R.H., Pratiwi; N.N., Padmadewi; A.A.G.Y., Paramartha (International Journal of Language and Literature, 2019)
This study was observational case study that examined the components of literacy-rich classroom environment at Aura Sukma Insani Kindergarten. The subjects of the research were the students and the teacher of B1 class of Aura Sukma Insani Kindergarten. The study examined the components of literacy-rich classroom environment and how it was exposed to the students during teaching and learning process. The instruments in this study consisted of researcher, observation sheet, interview guide, and literacy-rich classroom environment checklist. The results indicate that the Aura Sukma Insani Kindergarten applied all elements of classroom literacy environment, namely; classroom setup, classroom library, message center, display of students? work, storytelling chair, sign, label, and quotes, hints, writing equipment, reading and writing corner, reference materials, audiovisual equipment, and dramatic center. The Aura Sukma Insani Kindergarten also used several activities to expose the literacy-rich classroom environment materials, namely; checking the students? attendance using present board, setting day, date, and month on calendar board, using the printed media and classroom equipment during the learning process, and rewarding students? achievement using students? sticker collection and toys, reading log, book week, follow-up activity, and after-hours session class. However, the after-hours session activity that used in learning process was found less-effective due to the time and the management of the activity.